The question was:

x (3x^{2 }- 2x + 5)

My working out+answer:

=3x^{2 }- 2x^{2 }+ 5

=x^{2 }+ 5

Textbook answer:

=3x^{3 }- 2x^{2 }+ 5

Now I understand how they got that answer. When I multiply x with 3x^2, the exponent changes from 3x^2 ---> 3x^3.

But then doesn't that conflict with one of the indices laws?:

(a^{m})^{x} = a^{m × x}

So applying that rule:

▪x is to the power of 1 (since anything to the power of 1 is itself)

▪3x^2 is to the power of 2

• so it would be 3x^{2×1 }

• that's how I got 3x^{3}

Why does it not work?

Guest Nov 15, 2018

#1**+2 **

x * x^2 = x^(2+1) = x^3

this is NOT (x^m)^n this is x^m * x^n = x^(m+n)

so x^1 * x^2 = x^(2+1) = x^3

ElectricPavlov
Nov 15, 2018

#1**+2 **

Best Answer

x * x^2 = x^(2+1) = x^3

this is NOT (x^m)^n this is x^m * x^n = x^(m+n)

so x^1 * x^2 = x^(2+1) = x^3

ElectricPavlov
Nov 15, 2018